ЭТНОЛИНГВИСТИЧЕСКИЙ АНАЛИЗ НАИМЕНОВАНИЙ ЖИВОТНЫХ В ПРОЗАИЧЕСКИХ ФОЛЬКЛОРНЫХ ТЕКСТАХ АРХАНГЕЛЬСКОЙ И КАЛУЖСКОЙ ГУБЕРНИЙ - Павлова, Елена (Acta Neophilologica, 2018)
This report presents the descriptions of animal names from the standpoint of Russian ethnolinguistics and lingvo-folkloristics. The analysis is based on the central Russian texts and folklore of the northern prose (usually fairy tales), written at the turn of the 19th and early 20th centuries in the provinces of Arkhangelsk and Kaluga. The territorial specificity of the linguistic contexts of texts containing names of animals is discussed.